1997
DOI: 10.1038/sj.bjp.0701240
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of angiotensin II formation in human isolated bladder by selective inhibitors of ACE and human chymase: a functional and biochemical study

Abstract: 1 Functional recordings of smooth muscle tension and biochemical experiments on membrane fractions were performed to characterize angiotensin II (AII) formation in human isolated bladder smooth muscle. 2 A novel human chymase inhibitor CH 5450 (Z-Ile-Glu-Pro-Phe-CO 2 Me) and a recently developed human chymase substrate Pro 11 -,D-Ala 12 )-angiotensin I, claimed to be resistant to angiotensin converting enzyme (ACE) and carboxypeptidase, were used. 3 Angiotensin I (AI) (0.3 mM) induced a contractile response am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 27 publications
0
33
1
4
Order By: Relevance
“…2 and 3). Previous reports have indicated two shortcomings inherent in this approach to reveal the predominance of ACE and non-ACE pathways in different experimental models: first, the outcome is highly dependent on the concentrations of the substrate used, with higher concentrations favoring the apparent contribution of non-ACE pathways (26); and second, the overcapacity among the ANG II generating proteases tends to diminish the relative importance of selectively inhibited enzymes (61). Notwithstanding, the synergistic inhibitory effects of captopril and chymostatin (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3). Previous reports have indicated two shortcomings inherent in this approach to reveal the predominance of ACE and non-ACE pathways in different experimental models: first, the outcome is highly dependent on the concentrations of the substrate used, with higher concentrations favoring the apparent contribution of non-ACE pathways (26); and second, the overcapacity among the ANG II generating proteases tends to diminish the relative importance of selectively inhibited enzymes (61). Notwithstanding, the synergistic inhibitory effects of captopril and chymostatin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In other investigations, the partial or total blockade of ANG II formation by different combinations of ACE inhibitors with chymostatin or other protease inhibitors has provided clues as to the nature of the enzymes involved in ANG I conversion in a particular tissue or pharmacological preparation (23,45). Since the advent of [Pro 11 ,D-Ala 12 ]-ANG I, a biologically inactive precursor that selectively yields ANG II on incubation with chymases but not with ACE or carboxypeptidases (22), several reports (18,22,26,38,41,43,61,63) have described the relative contribution of chymases in ANG II formation in isolated preparations derived from various species.The vascular endothelium actively participates in the control of vascular tone through the synthesis and metabolism of several vasoactive substances (1). In particular, the vascular endothelium has been shown to be a major site of conversion of circulating ANG I to ANG II by ACE located on its luminal surface (2).…”
mentioning
confidence: 99%
“…Angiotensins. An autocrine/paracrine reninangiotensin system has been identified in the urinary bladder (Weaver-Osterholtz et al, 1996), and angiotensin II (ATII) formation was demonstrated in human isolated detrusor smooth muscle Lindberg et al, 1994;Waldeck et al, 1997). ATII receptors have been demonstrated by different methods in animal as well as human detrusor (Anderson et al, 1984;Lam et al, 2000).…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…ATII was reported to contract the urinary bladder of several species, but with a wide range of relative potencies (Erspamer et al, 1973;Anderson et al, 1984). Several investigators (Erspamer et al, 1981;Andersson et al, 1992, Saito et al, 1993Lindberg et al, 1994;Waldeck et al, 1997), but not all , have shown that in human detrusor muscle, ATII was a potent and effective contractile agent. In dog bladder, the responses to both ATII and ATI were minor or lacking (Steidle et al, 1990), illustrating the wide variation in response to the peptide between species.…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…Local tissue RAS was found in the blood vessels, heart, kidneys, small intestines, pancreatic tissue, liver, ovaries and brain (Paul at al., 2006). Other enzymes involved in RAS and physiologicaly active metabolites of Ang I and Ang II were also found (Waldeck et al, 1997;Miyazaki & Takai, 2006).…”
Section: The Effects Of Some Neuropeptides On Motor Activity Of Smootmentioning
confidence: 95%